Analytic nuclear gradients of the algebraic-diagrammatic construction scheme for the polarization propagator up to third order of perturbation theory - Rehn, Dirk R.; Dreuw, Andreas (The journal of chemical physics, 2019)
Analytic gradient expressions for the algebraic diagrammatic construction (ADC) scheme for the polarization propagator up to third order are derived using a Lagrangian approach. An implementation within the Q-CHEM electronic structure package for excited-state nuclear gradients of the ADC(2), ADC(2)-x, and ADC(3) models based on restricted and unrestricted Hartree-Fock references is presented. Details of the implementation and the applicability of the newly derived gradients for geometry optimizations and the quality of the resulting structures are discussed.